The Fungal CYP51s: Their Functions, Structures, Related Drug Resistance, and Inhibitors - Zhang, Jingxiang; Li, Liping; Lv, Quanzhen; Yan, Lan; Wang, Yan; Jiang, Yuanying (Frontiers in Microbiology, 2019)
CYP51 (Erg11) belongs to the cytochrome P450 monooxygenase (CYP) superfamily and mediates a crucial step of the synthesis of ergosterol, which is a fungal-specific sterol. It is also the target of azole drugs in clinical practice. In recent years, researches on fungal CYP51 have stepped into a new stage attributing to the discovery of crystal structures of the homologs in C. albicans, C. neoformans and A. fumigatus. This review summarizes the functions, structures of fungal CYP51 proteins, and the inhibitors targeting these homologs. In particular, several drug-resistant mechanisms associated with the fungal CYP51s are introduced. The sequences and crystal structures of CYP51 proteins in different fungal species are also compared. These will provide new insights for the advancement of research on antifungal agents.